V.I. Lenin at the right talking to V.M. Zagorskij, Secretary of the Moscow Committee of the R.C.P.(B.) on the Red Square during a May Day demonstration. Compare: 69/39 A, page 186 - Savel'ev, A.I.,
V.I. Lenin at the right talking to V.M. Zagorskij, Secretary of the Moscow Committee of the R.C.P.(B.) on the Red Square during a May Day demonstration. Compare: 69/39 A, page 186.